2009
DOI: 10.1080/15438620902897516
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Motor Skill Proficiency of Hong Kong Children Aged 6–9 Years

Abstract: This study investigated the fundamental motor skill proficiency of Hong Kong children aged 6-9.Ninety-one and 76 Chinese male and female students (mean age = 7.6 years) from six local primary schools in Hong Kong participated in this study. The Test of Gross Motor Development -Second Edition (TGMD-2) was administrated to assess the mastery of gross motor skills by an experienced physical education instructor. The performance was videotaped, and was rated by the same physical education instructor again (one wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
4
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 15 publications
8
39
4
11
Order By: Relevance
“…Afonso et al (2009) showed that the best skill in Madeira Islandconsidering girls and boys separately -does not relate to the most popular sport. Although Ulrich (2000) and Wong and Cheung (2006) have not evaluated the prevalence of mastery by gender, the results found by Pang and Fong (2009) in Hong Kong and Butterfield, Angell, and Mason (2012) in the United States showed that sex also did not influence the prevalence of mastery. Based on these results, it is possible to argue that sex was not a factor that influenced the prevalence of mastery in the skill associated with the most popular sport.…”
Section: Resultsmentioning
confidence: 98%
“…Afonso et al (2009) showed that the best skill in Madeira Islandconsidering girls and boys separately -does not relate to the most popular sport. Although Ulrich (2000) and Wong and Cheung (2006) have not evaluated the prevalence of mastery by gender, the results found by Pang and Fong (2009) in Hong Kong and Butterfield, Angell, and Mason (2012) in the United States showed that sex also did not influence the prevalence of mastery. Based on these results, it is possible to argue that sex was not a factor that influenced the prevalence of mastery in the skill associated with the most popular sport.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, Weikart [3] has pointed out that first and second graders need to acquire a wide variety of physical skills, including such object control skills as throwing, kicking, and catching a ball, and such movement skills as walking, running, and hopping. Moreover, the successful development of FMSs is not only essential to the acquisition of complex movement skills, but also promotes muscle coordination and assists in the development of interpersonal, cognitive, and emotional skills [4]. FMS can be divided into locomotor skills (LS) and object-control skills (OCS) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The TGMD-2 is an objective and normalized tool which is widespread in extensive research conducted in preschool and early childhood education [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Similarly to other researchers [26,27,28,39], we also analysed the raw scores of the TGMD-2 locomotor and object control skills subscales.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature, we noticed that other researchers verified the reliability and validity of the TGMD-2 test for their populations. Studies were conducted, inter alia, in Belgium [35], China [36,38], the Czech Republic [37], Brazil [39] and South Korea [40]. In Poland there is a lack of diagnosis of fundamental movement skills of children in preschool and elementary school.…”
Section: Discussionmentioning
confidence: 99%